THERAPEUTIC HORTICULTURE AS AN INNOVATIVE METHOD OF REHABILITATION: PROSPECTS OF INTEGRATION INTO RURAL TOURISM INUKRAINE - ZHURBA, Igor; KOSOVSKA, Karina (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study explores the potential of therapeutic horticulture as an innovative approach to rehabilitation. The article examines global experiences in implementing horticultural therapy, highlighting its impact on physical and mental health. Special attention is given to the therapeutic mechanisms of horticulture and its potential integration into Ukraine’s rehabilitation system. Additionally, the study considers the role of rural green tourism as a complementary method that enhances the recovery process by fostering human interaction with nature. The study identifies key challenges and opportunities in developing horticultural therapy and provides recommendations for its implementation in rehabilitation programs. The purpose of this study is to justify the relevance of therapeutic horticulture in rehabilitation, determine its role in improving physical and psychological well-being, and assess the feasibility of its integration into Ukraine’s healthcare and social sectors. The research focuses on identifying the most effective therapeutic approaches, analyzing existing barriers to implementation, and outlining strategic directions for the development of horticultural therapy as a structured rehabilitation method. The study also explores the synergy between horticultural therapy and rural green tourism, highlighting its potential in sustainable rehabilitation models.